2020
DOI: 10.3390/ani10081357
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Economic Impact of COVID-19 on Spanish Small Ruminant Flocks

Abstract: The human pandemic COVID-19 caused by the severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) started in China in 2019 and has rapidly spread around the world, leading to extreme control measures such as population confinement and industry activity closure. Although small ruminants are not sanitary affected by this virus, the short-term economic impact derived by COVID-19 on Spanish flocks is estimated in this study, using data provided by producers and two major slaughterhouses. Milk prices of dairy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 19 publications
1
16
0
1
Order By: Relevance
“…The livestock industry suffered great economic impacts ( Biswal et al, 2020 , Rude, 2020 ), irrespective of whether the actual livestock was affected by the virus directly. For example, a study in Spain reported that, although small ruminants are not sanitary affected by this virus, global data evidenced a lamb price drop ranging from 16.8% to 26.9% and a 12.5% to up to 40% drop in the goat kid meat market ( Vidaurreta et al, 2020 ). Some have also reported that decreased access to pastoral areas due to COVID-19 measures will impact desert locust control, disaster relief or disease control ( Griffith et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The livestock industry suffered great economic impacts ( Biswal et al, 2020 , Rude, 2020 ), irrespective of whether the actual livestock was affected by the virus directly. For example, a study in Spain reported that, although small ruminants are not sanitary affected by this virus, global data evidenced a lamb price drop ranging from 16.8% to 26.9% and a 12.5% to up to 40% drop in the goat kid meat market ( Vidaurreta et al, 2020 ). Some have also reported that decreased access to pastoral areas due to COVID-19 measures will impact desert locust control, disaster relief or disease control ( Griffith et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This had an impact on human wellbeing, animal welfare, and the environment ( Marchant-Forde Jeremy and Boyle Laura, 2020 ). The reduction on processing capacity affected transport, with some animals/hauliers travelling longer distances to plants in operation, live animals kept living for longer periods with an impact on stocking densities and space on farm, leading, for example, to increased heat production and associated reduced environmental factors as well as the need for on farm culling of animals ( Parry, 2020 ; Marchant-Forde Jeremy and Boyle Laura, 2020 ; Vidaurreta et al, 2020 ). Some reported farmers using abortion as a population control measure or inhumane culling methods that would impact animal welfare, such as ventilation shut down ( Hashem et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The short-term impact of COVID-19 on Spanish small ruminant flock production was investigated (15). To which, the authors observed the sudden impact on meat markets, particularly in small ruminant flocks.…”
Section: Impact Of Covid-19 On Meat Productionmentioning
confidence: 99%
“…Even without a direct effect on health, preliminary data obtained from a limited number of Spanish farms during the confinement showed that this sector suffered a short-term economic impact that resulted in lower milk and meat prices paid to producers, considering that the year 2020 started with high prices for small ruminant milk and meat, following the trend of high prices registered during the last years. [12]. Variation in prices is considered to be a normal aspect of well-functioning markets, but price volatility becomes problematic when price movements are large and unpredictable [13].…”
Section: Introductionmentioning
confidence: 99%